Nonlinear Super Integrable Couplings of Super Classical-Boussinesq Hierarchy. (7th April 2014) - Xing, Xiuzhi; Wu, Jingzhu; Geng, Xianguo
Abstract : Nonlinear integrable couplings of super classical-Boussinesq hierarchy based upon an enlarged matrix Lie super algebra were constructed. Then, its super Hamiltonian structures were established by using super trace identity. As its reduction, nonlinear integrable couplings of the classical integrable hierarchy were obtained.